Responses To Future Challenges Inclusive Schools For Children With Special Needs - Suchyadi, Yudhie; Santa, Santa; Muhajang, Tatang; Anwar, Wawan Syahiril; Indriani, Rini Sri (UNIVERSITAS PAKUAN, 2023)
Inclusive schools are educational services provided for children with special needs in obtaining proper education. government policy contained in Law Number 20 of 2003 in article 32 and Permendiknas number 70 of 2009 namely by providing opportunities and opportunities for children with special needs to obtain education in regular schools. In inclusive schools, it is possible for children with special needs to learn together with normal children, and be treated like normal children. This shows the positive impact of inclusive schools on children with special needs from a psychological perspective. Various problems that have arisen after more than 10 years of implementation in inclusive education practices indicate that there are challenges that hinder the implementation of inclusive education in Indonesia. One of the factors is the competence of teachers who have not been able to handle children with special needs in regular classes. The success of implementing an inclusive school depends on the competency of the teacher and the cooperation between the school and the government.